METODE PELAKSANAAN PEKERJAAN LAPIS PONDASI ATAS (LPA) STUDI KASUS PEKERJAAN JALAN POROS WUNA-LAFINDE JALUR II KABUPATEN MUNA BARAT - La Ode Yasir; La Welendo; Umran Sarita (PRODI D3 TEKNIK SIPIL, 2020)
Abstract This study aimed at to find out the management problems in material mobilization and time implementation management which were applied to overcoming problems during Top Foundation Layer method implementation for improving Wuna - Lafinde road, line II, in West Muna Regency. S curve of contract document was used in analyzing the time implementation management. Analysis of costs and heavy equipment productivity used in project enforcement namely blending equipment, Wheel Loaders, barges, Excavators, dump trucks in 3.5, ton loads, dump trucks in 10 ton loads, graders, Vibrator Rollers and Water Tank Truck, refers to Minister of Public Works and Public Housing regulation No. 28 of 2016 in Highways Sector.Analysis result showed that management problems in material mobilization were the delayed of contractors in started their work, lack of dump trucks in capacity of 10 tons and the scarcity of dump trucks in 3.5 tons capacity. Time management in overcoming the problem of material mobilization is the contractor have to provide the ready mix materials before entering the first week of the S curve in contract document, add a dump truck in 10 tons capacity and augment a dump truck in 3.5 tons capacity. Abstrak Karya ilmiah ini bertujuan untuk mengetahui permasalahan manajemen dalam mobilisasi material dan manajemen waktu pelaksanaan yang diterapkan dalam mengatasi masalah yang timbul pada saat pelaksanaan pekerjaan lapis pondasi atas pada pekerjaan peningkatan jalan poros Wuna – Lafinde jalur II Kabupaten Muna Barat. Analisis manajemen waktu pelaksanaan menggunakan kurva S dokumen kontrak, Analisis biaya dan produktivitas alat berat yang digunakan dalam pelaksanaan pekerjaan yaitu blending equipment, Wheel Loader, kapal tongkang, Excavator, dump truck 3.5 ton, dump truck 10 ton, Motor Grader, Vibrator Roller dan Water Tank Truck, dengan mengacu pada Peraturan Menteri Pekerjaan Umum dan Perumahan Rakyat No. 28 Tahun 2016 Bidang Binamarga. Hasil analisa menunjukan bahwa permasalahan manajemen pada mobilisasi material yaitu keterlambatan kontraktor pelaksana memulai pekerjaan, kurangnya dump truck kapasitas 10 ton dan kurangnya dump truck kapasitas 3.5 ton. Manajemen waktu dalam mengatasi masalah mobilisasi material yaitu kontraktor pelaksana harus menyediakan ready mix material sebelum masuk minggu pertama kurva S dokumen kontrak, penambahan dump truck kapasitas 10 ton dan penambahan dump truck kapasitas 3.5 ton.